Features of the psycho-physiological functions of elite athletes - Paralympians (on the example of fencing and table tennis) - M. Lytovchenko; E. Breus; Zh.L. Kozina; I.M. Sobko; O.O. Ryepko (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
The aim of the work is to identify the characteristics of psycho-physiological indicators in Paralympic athletes compared with athletes - Olympians and the influence of the characteristics of lesions of the upper and lower extremities on psychophysiological indicators. Material and methodsThe study involved 15 elite swordsmen performing in Olympic sports, 15 elite swordsmen - Paralympians; 33 elite athletes with disorders of the musculoskeletal system of the sixth (15 people) and tenth (18 people) functional classes in table tennis, age 21-25 years. The parameters characteristic for determining the psycho-physiological state were determined using computer programs for psycho-physiological testing. Dispersion analysis was also used. The influence of the functional class of athletes on the reaction rate in different test modes was determined. Results. Significant differences were found between Olympic swordsmen and Paralympian swordsmen in terms of "Minimum signal exposure time in a test with feedback" (p <0.05) and a complex reaction time when selecting 1 object out of 3; among the Olympic fencers, these figures are significantly higher compared with the Paralympians. It is shown that belonging to a certain functional class of athletes - Paralympians in table tennis affects the rate of stability of the reaction rate and the rate of time to reach the minimum signal exposure in the test for the speed of selection reaction with feedback. The speed of response to a visual signal, the number of errors during the test for reaction speed, the mobility of nerve processes in athletes - Paralympians in table tennis reliably depends on the degree of damage to the upper and lower extremities. The worst results in psychophysiological indicators were found in athletes with impaired operation of both lower extremities. Unilateral damage to the extremities and congenital underdevelopment of the extremities have a lesser effect on the psychophysiological functions. Conclusions. When training Paralympians - fencers and holding competitions, it is necessary to take into account not only the physical, but also the psychophysiological characteristics of the fencers - Paralympians. When training and functional classification of Paralympic athletes in table tennis, it is important to consider not only their affiliation to a certain functional class, but also the degree of disruption of the upper and lower extremities and the level of psycho-physiological functions.